Islamic Cognitive Behavior Therapy Counseling to Improve the Self-Regulated Learning Santri of Tsanawiyah Level - Isna Sufyaningsih Munawar; Imas Kania Rahman; A. Rahmat Rosyadi (Tarbiyah Departement collaboration with AMCA, 2023)
This research was to find how many level of self-regulated learning in MTs santri at the Daarul Rahman Bogor Islamic Boarding School, and to find how manner to increase the self-regulated learning of MTs santri at the Daarul Rahman Islamic Boarding School Bogor after receiving Islamic cognitive behavior therapy counseling and to formulate how Islamic cognitive behavior therapy counseling which is effective to improve the santri from self-regulated learning at Mts level. This research used a quantitative with method that is quasi-experimental and a nonequivalent control group design model through a pre-posttest approach and compared with the control group. Based on the results of this research, that the level of self-regulated learning of MTs santri in the low category was 3 santri, the medium was 11 santri and the high was 16 santri. After implementing Islamic cognitive behavior therapy treatment, there was an increase, namely, in the medium category from 11 santri it decreased to 2 santri and in the high category from 16 santri it increased rapidly to 27 santri. The experimental group has a mean of 90.37 while the control group has a mean of 83.57. Thus, can be interpreted what the provision of Islamic cognitive behavior therapy to santri will increase self-regulated learning.